2010
DOI: 10.1080/15459624.2010.487789
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Crystalline Silica Exposure Assessment for a Historical Cohort Epidemiologic Study in the German Porcelain Industry

Abstract: A time-dependent quantitative exposure assessment of silica exposure among nearly 18,000 German porcelain workers was conducted. Results will be used to evaluate exposure-response disease risks. Over 8000 historical industrial hygiene (IH) measurements with original sampling and analysis protocols from 1954-2006 were obtained from the German Berufs- genossenschaft der keramischen-und Glas-Industrie (BGGK) and used to construct a job exposure matrix (JEM). Early measurements from different devices were converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Mean air RCS concentration measured in these sectors (GM50.045 and GM50.017, respectively) are in line with concentrations reported in recent years in other European countries and in North America. [13][14][15][16][17] According to the 2001 industrial activity census, approximately 863 250 Italian workers are employed in construction. 11 Using our data, a reliable estimate of Italian workers exposed to silica was achievable only for a specific subsector of this activity (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean air RCS concentration measured in these sectors (GM50.045 and GM50.017, respectively) are in line with concentrations reported in recent years in other European countries and in North America. [13][14][15][16][17] According to the 2001 industrial activity census, approximately 863 250 Italian workers are employed in construction. 11 Using our data, a reliable estimate of Italian workers exposed to silica was achievable only for a specific subsector of this activity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] We estimate that about 30 000 workers are exposed to crystalline silica in the manufacture of non-metallic minerals in Italy (NACE code 26) 12 Similarly, in our study, exposure levels in the manufacture of nonmetallic minerals were found to vary between and within occupations, leading to an overall mean concentration lower than in construction, as well as a smaller percentage of TLV overwhelming values. This may be due to the significant decrease of airborne RCS concentrations reported in the ceramic industry over time, 14,22 and to the high variation in whether workers use dry or automated/remotely controlled working methods. 15 A number of female workers were also estimated to be exposed to RCS in this sector, particularly in the ceramic (N52458) and the artistic stone working industry (N5913).…”
Section: Discussionmentioning
confidence: 99%
“…Also taking into account previous reports on the porcelain worker cohort, [5][6][7] it becomes obvious that the most crucial point in the presented study seems to be the healthy-worker effect. The fixed cohort of workers in the German porcelain industry consists solely of "prevalent" hires, that is, of those employees already at work at the start of the follow-up.…”
Section: Healthy-worker Effectmentioning
confidence: 72%
“…22 In short, more than 8000 combined static (stationary area) and personal total, respirable and silica dust industrial hygiene measurements were available for about 100 discrete production area or job task code combinations beginning in 1954 and covering all years through the end of folowup. Original sampling and analysis protocols were available for these measurements.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Extensive industrial hygiene exposure data for this cohort have been obtained and used to derive quantitative exposure estimates for each cohort member. 22 Furthermore, evaluation of a large archive of radiographic examinations obtained as part of a medical surveillance program for German porcelain workers including a substantial proportion of this cohort facilitated radiographic determination of silicosis morbidity. Combining the mortality data, the silicosis morbidity data, and the quantitative exposure assessment allows quantitative evaluation of potential relationships between estimates of respirable crystalline silica exposure and silicosis morbidity and lung cancer mortality.…”
mentioning
confidence: 99%